Visual research an introduction to research methods in graphic design - Bestley, Russell; McNeil, Paul (Graphic designer); Noble, Ian 1960- Visual research : an introduction to research methods in graphic design (London, UK Bloomsbury Visual Arts, trademark of Bloomsbury Publishing Plc, 2022)
Packed with more than 200 colour illustrations, Visual Research explores a range of research methods that can be used by graphic designers and visual communicators in the development of clear and purposeful design solutions. The book introduces key terms and theories that underlie design research; examining the importance of visual grammar and design literacy, audience, communication theory and semiotics"--Provided by publisher.
Third edition entered under Noble, Ian.
Includes bibliographical references (pages 244-245) and index.
Keywords: Graphic arts -- Research; Design -- Research